TIMP3 Is Reduced in Atherosclerotic Plaques From Subjects With Type 2 Diabetes and Increased by SirT1 - Cardellini, Marina; Menghini, Rossella; Martelli, Eugenio; Casagrande, Viviana; Marino, Arianna; Rizza, Stefano; Porzio, Ottavia; Mauriello, Alessandro; Solini, Anna; Ippoliti, Arnaldo; Lauro, Renato; Folli, Franco; et al. (Diabetes (New York, N.Y.), 2009)
TIMP3 Is Reduced in Atherosclerotic Plaques From Subjects With Type 2 Diabetes and Increased by SirT1 Marina Cardellini 1 , Rossella Menghini 1 , Eugenio Martelli 2 , Viviana Casagrande 1 , Arianna Marino 1 , Stefano Rizza 1 , Ottavia Porzio 1 , Alessandro Mauriello 3 , Anna Solini 4 , Arnaldo Ippoliti 2 , Renato Lauro 1 , Franco Folli 5 and Massimo Federici 1 1 Department of Internal Medicine, University of Rome Tor Vergata, Rome, Italy; 2 Department of Surgery, University of Rome Tor Vergata, Rome, Italy; 3 Department of Biopathology and Diagnostic Imaging, University of Rome Tor Vergata, Rome, Italy; 4 Department of Internal Medicine, University of Pisa, Pisa, Italy; 5 Division of Diabetes, Department of Medicine, University of Texas Health Science Center, San Antonio, Texas. Corresponding author: Massimo Federici, federicmatuniroma2.it . Abstract OBJECTIVE Atherosclerosis is accelerated in subjects with type 2 diabetes by unknown mechanisms. We identified tissue inhibitor of metalloproteinase 3 (TIMP3), the endogenous inhibitor of A disintegrin and metalloprotease domain 17 (ADAM17) and other matrix metalloproteinases (MMPs), as a gene modifier for insulin resistance and vascular inflammation in mice. We tested its association with atherosclerosis in subjects with type 2 diabetes and identified Sirtuin 1 (SirT1) as a major regulator of TIMP3 expression. RESEARCH DESIGN AND METHODS We investigated ADAM10 , ADAM17 , MMP9 , TIMP1 , TIMP2 , TIMP3 , and TIMP4 expression levels in human carotid atherosclerotic plaques ( n = 60) from subjects with and without diabetes. Human vascular smooth muscle cells exposed to several metabolic stimuli were used to identify regulators of TIMP3 expression. SirT1 small interference RNA, cDNA, and TIMP3 promoter gene reporter were used to study SirT1-dependent regulation of TIMP3 . RESULTS Here, we show that in human carotid atherosclerotic plaques, TIMP3 was significantly reduced in subjects with type 2 diabetes, leading to ADAM17 and MMP9 overactivity. Reduced expression of TIMP3 was associated in vivo with SirT1 levels. In smooth muscle cells, inhibition of SirT1 activity and levels reduced TIMP3 expression, whereas SirT1 overexpression increased TIMP3 promoter activity. CONCLUSIONS In atherosclerotic plaques from subjects with type 2 diabetes, the deregulation of ADAM17 and MMP9 activities is related to inadequate expression of TIMP3 via SirT1. Studies in vascular cells confirmed the role of SirT1 in tuning TIMP3 expression. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received February 24, 2009. Accepted June 23, 2009. © 2009 by the American Diabetes Association.